Shielding Unit Engineering of NIR-II Molecular Fluorophores for Improved Fluorescence Performance and Renal Excretion Ability - Liu, Chunchen; Ma, Huilong; Hu, Zhubin; Tian, Rui; Ma, Rui; Xu, Yifan; Wang, Xinyuan; Zhu, Xingfu; Yu, Panpan; Zhu, Shoujun; Sun, Haitao; Liang, Yongye (Frontiers in Chemistry, 2021)
Molecular fluorophores emitting in the second near-infrared (NIR-II) window with good renal excretion ability are favorable for in vivo bio-imaging and clinical applications. So far, renally excretable fluorophores are still less studied. Understanding the influences of molecular structure on optical properties and renal excretion abilities are vital for fluorophore optimization. Herein, a series of shielding unit-donor-acceptor-donor-shielding unit (S-D-A-D-S) NIR-II molecular fluorophores are designed and synthesized with dialkoxy chains substituted benzene as the S unit. The anchoring positions of dialkoxy chains on benzene are tuned as meso-2,6, para-2,5, or ortho-3,4 to afford three fluorophores: BGM6P, BGP6P and BGO6P, respectively. Experimental and calculation results reveal that alkoxy side chains anchored closer to the conjugated backbone can provide better protection from water molecules and PEG chains, affording higher fluorescence quantum yield (QY) in aqueous solutions. Further, these side chains can enable good encapsulation of backbone, resulting in decreased binding with albumin and improved renal excretion. Thus, fluorophore BGM6P with meso-2,6-dialkoxy chains exhibits the highest QY and fastest renal excretion. This work emphasizes the important roles of side chain patterns on optimizing NIR-II fluorophores with high brightness and renal excretion ability.